Collective demands and secret codes: The multiple uses of "community" in "community mobilization". (April 2018) - Vijayakumar, Gowri
Highlights: HIV prevention staff and activists used the concept of "community" in three ways. First, "community" placed responsibility for prevention on groups at risk. Second, "community" undergirded collective demands for support and resources. Third, "community" served as code for subversive sexual categories in public space. "Community" is a multivalent concept used in struggles for control and survival. Abstract: The romance of "community mobilization" continues to pervade development and public health programs. Critics argue that "community" has become a buzzword devoid of content or a mechanism of neoliberal governmentality. This article revisits these approaches to community mobilization, using ethnographic data from a context in which "community mobilization" has met with wide acclaim: HIV prevention programs in India. Focusing on how the concept of community is used in everyday practice reveals its multivalence and flexibility. I show that, for many planners and administrators of HIV prevention programs, "community mobilization" is a strategy for placing responsibility for HIV prevention onto groups at risk, but, for those groups, it also has two alternative usages: as the basis for making collective demands, and as a code word for membership in a subversive sexual category. These latter two uses undergird the formation of "communities" that make new demands on the state. While scholars tend to characterize community mobilization programs in terms of their intent, as either mostly empowering or mostly a mechanism of domination, this article shifts the focus to how the concept of community is used, demonstrating its multiple usages within the same program. I show that groups bring to bear on the concept of "community" not only abstracted NGO concepts, but also a history of using "community" in India as a political category of membership. Rather than rejecting or celebrating the concept of "community", this article uses ethnography to show how community is put to use and given meaning through everyday struggles for control and survival.